The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/bjophthalmol-2013-304652
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of ocular volume from axial length

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
(17 reference statements)
4
23
0
Order By: Relevance
“…The data indicate that, similar to our findings on total ocular volume (Nagra et al. ), accurate estimates of TSA cannot be made from the application of a spherical model based simply on longitudinal axial length, particularly with regard to shorter axial lengths (Table ,. 2,Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The data indicate that, similar to our findings on total ocular volume (Nagra et al. ), accurate estimates of TSA cannot be made from the application of a spherical model based simply on longitudinal axial length, particularly with regard to shorter axial lengths (Table ,. 2,Fig.…”
Section: Discussionsupporting
confidence: 81%
“…; Nagra et al. ). A T2‐weighted scan was used to demarcate fluid‐based intraocular structures for each eye and thus provide high‐contrast delineation of the internal surface of the eye including the vitreous‐retina interface.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Nagra et al 5 emphasize the likely importance of ocular volume rather than axial length and in a study of total ocular volume from MRI scans of 67 adults they observed axial length and corneal radius to predict ocular volume. The authors postulate that ocular volume rather than axial length might be a structural correlate for IOP elevation after invitreal injection.…”
mentioning
confidence: 99%